Accelerated of Sex Reversal use 17α-methyltestosterone Induced Female, Orange-Spotted Grouper Epinephelus coioides - Odang Carman; Andri Iskandar; Ching-Fong Chang; Guan-Chung Wu; Muslim Muslim; Dian Eka Ramadhani (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Sex reversal for orange-spotted grouper Epinephelus coioides The application of 17α-methyltestosterone induce sex change The stability of sex change need more investigation Abstract The occurance of hermaphrodites in grouper fish causes a scarcity of male parents, so an alternative is needed to accelerate sexchange to male at a young age. The present study was expected to scrutinize the mechanisms of sex-change in fish in the early change process, and whether the testis converted from immature ovary using 17α-methyltestosterone (MT) would recover after the termination of MT treatment. MT-induced sex-change and 5-aza-2'-deoxycytidine (5-Aza) were connected as DNA methylation inhibitors to comprehend the alternation of gonadal soma cells. The orange-spotted groupers were used at the developmental ages and fed a diet containing MT at 50 mg/kg for three months and then a normal diet for a month. In the first week and second week fish injected with 5-Aza intraperitoneally during the MT-oral administration. Most of the fishes in the control group had immature ovaries, but all the females fed with MT, had immature spermatogenesis. However, one month after the withdrawal of MT treatment, the sex of the fish returned to female-like even though the fish have undergone MT-induced masculinization. This outcome demonstrates precocious sex-change from under yearling, orange-spotted grouper utilizing oral MT treatment is impermanent. All the females of 5-aza treatments showed no spermatogenic cells. In this study, lower growth rates were demonstrated by the MT-treated groups. The impact of this metabolic change was clear after the end of the hormone oral administration since the decreased growth of the groups treated for three months.